Islamic studies : a history of Religions approach - Martin, Richard C.; Martin, Richard C. (Upper Saddle River, New Jersey : Prentice-Hall, 1996)
En1. ed. of: Islam, a cultural perspective. c1982
Includes bibliographical references (p.256-261) and index
Keywords: Islam